Intraperitoneal sertraline and fluvoxamine increase contextual fear conditioning but are without effect on overshadowing between cues - Cassaday, Helen J.; Thur, Karen E. (Elsevier, 2015)
Treatment with selective serotonin reuptake inhibitors (SSRIs) can reduce contextual conditioning. Since contexts present a variety of potentially competing cues, impaired overshadowing may provide an account of such effects. The present study therefore compared the effects of two SSRIs on overshadowing and contextual conditioning, testing suppression of an ongoing behavioral response (licking) by cues previously paired with foot shock. Conditioning to a 5s light stimulus was reduced when this was presented in compound with a 5s noise, thus overshadowing was demonstrated. In two experiments, this overshadowing was unaffected by treatment with either sertraline or fluvoxamine. However, unconditioned suppression to the noise (tested in the control group previously conditioned to the light alone) was reduced after sertraline (10mg/kg, i.p.). The successful demonstration of overshadowing required the use of a second conditioning session or an additional conditioning trial within the same conditioning session. Neither weak nor strong overshadowing (of the light by the tone) was affected by any drug treatment. Moreover, counter to prediction, conditioning to contextual cues was increased rather than impaired by treatment with sertraline (10mg/kg, i.p.) and fluvoxamine (30mg/kg, i.p.).